Duration of intravenous antibiotic therapy in people with cystic fibrosis - Plummer, Amanda (Cochrane Database Syst Rev, 2016)
BACKGROUND: Respiratory disease is the major cause of mortality and morbidity in cystic fibrosis. Life expectancy of people with cystic fibrosis has increased dramatically in the last 40 years. One of the major reasons for this increase is the mounting use of antibiotics to treat chest exacerbations caused by bacterial infections. The optimal duration of intravenous antibiotic therapy is not clearly defined. Individuals usually receive intravenous antibiotics for 14 days, but treatment may range from 10 to 21 days. A shorter duration of antibiotic treatment risks inadequate clearance of infection which could lead to further lung damage. Prolonged courses of intravenous antibiotics are expensive and inconvenient and the incidence of allergic reactions to antibiotics also increases with prolonged courses. The use of aminoglycosides requires frequent monitoring to avoid some of their side effects. However, some organisms which infect people with cystic fibrosis are known to be multi‐resistant to antibiotics, and may require a longer course of treatment. This is an update of previously published reviews. OBJECTIVES: To assess the optimal duration of intravenous antibiotic therapy for treating chest exacerbations in people with cystic fibrosis. SEARCH METHODS: We searched the Cochrane Cystic Fibrosis and Genetic Disorders Group Trials Register which comprises references identified from comprehensive electronic database searches, handsearches of relevant journals, abstract books and conference proceedings. Most recent search of the Group's Cystic Fibrosis Trials Register: 05 May 2016. SELECTION CRITERIA: Randomised and quasi‐randomised controlled trials comparing different durations of intravenous antibiotic courses for acute respiratory exacerbations in people with CF, either with the same drugs at the same dosage, the same drugs at a different dosage or frequency or different antibiotics altogether, including studies with additional therapeutic agents. DATA COLLECTION AND ANALYSIS: No eligible trials were identified. MAIN RESULTS: No eligible trials were identified. AUTHORS' CONCLUSIONS: There are no clear guidelines on the optimum duration of intravenous antibiotic treatment. Duration of treatment is currently based on unit policies and response to treatment. Shorter duration of treatment should improve quality of life and compliance; result in a reduced incidence of drug reactions; and be less costly. However, this may not be sufficient to clear a chest infection and may result in an early recurrence of an exacerbation. This systematic review identifies the need for a multicentre, randomised controlled trial comparing different durations of intravenous antibiotic treatment as it has important clinical and financial implications.